The Effects of procedure and sensation information on the anxiety level of patients for electrocardiogram - Cadacio, Manolita Gonzales
This study investigated the effects of procedure and sensation information on the anxiety level of patients undergoing an EKG or electrocardiogram. This study is significant in that, it augmented existing literature on a structured tool to prepare patients for EKG. It also provided help to the nurses and other allied medical personnel in administering a nursing intervention that reduces the anxiety level of patients undergoing EKG. It was hypothesized that procedure and sensation information reduces the anxiety level of patients undergoing EKG procedure more when compared with clients given only explanation regarding the EKG. Those patients who were not informed nor instructed about EKG procedure werehypothesized to register high levels of anxiety. The subjects comprised of 105 middle adult male and female patients at the EKG Central Station of a large government teaching hospital in Metro Manila, who were grouped as: Study Groups 1 and 2 (Experimental) and Study Group 3 (Control). Each group was composed of 35 members ...
Thesis (Master of Arts in Nursing) -- University of the Philippines Manila
Keywords: Anxiety -- Testing; Electrocardiography; Anxiety reduction